Micropropagation of yardlong bean (Vigna unguiculata (L.) Walsp. ssp. Sesquipedalis L. Verdc.) through in vitro culture - Jahan, I; Alam, N; Roy, PK (Bangladesh Journal of Botany, 2018)
An in vitro propagation protocol has been established for yardlong bean (Vigna unguiculata ssp. sesquipedalis L. Walp. Verdc.) using shoot tip, nodal and leaf segment explants of the superior plant type obtained from crossing of two selected parental lines. Explants were cultured on MS medium supplemented with different concentrations and combinations of BAP, Kn and Zeatin and NAA, IAA, IBA. The highest percentage (86) of shoot regeneration with maximum shoots per culture (12 ± 0.43) was obtained from nodal explants on MS medium supplemented with 0.5 mg/l BAP and 0.2 mg/l NAA. Addition of 10% coconut water and 75 mg/l urea to the medium enhanced shoot multiplication and elongation, respectively. Rooting of the regenerated shoots was optimum on half-strength MS enriched with 3.0 mg/l IBA. Regenerated plantlets were successfully acclimatized. After acclimation, plantlets were transplanted in the experimental field where the survival rate was 80%.